¿Pueden ir de la mano el desarrollo y la política de seguridad? El desafío de la reforma del sector de la seguridad - Faltas, Sami (Revista Española de Desarrollo y Cooperación, 2023)
In this short article, I will look at a specific result of the quest for a comprehensive approach to security and development, namely donor support for Security Sector Reform (SSR). While I must confess to being an advocate of SSR, I will dwell not only on its useful potential, but also on the considerable difficulties it faces. I will also flag some conceptual and policy problems inherent to the donors’ doctrine of SSR. This will lead me to suggest that in 2011, four years after the publication of the seminal OECD DAC Handbook on Security System Reform, we need a critical review of the Western approach to SSR.